1,2,3-Triazole substituted phthalocyanine metal complexes as potential inhibitors for anticholinesterase and antidiabetic enzymes with molecular docking studies - Koçyiğit, Ümit M.; Taslimi, Parham; Tüzün, Burak; Yakan, Hasan; Muğlu, Halit; Güzel, Emre (Informa UK Limited, 2020)
In recent years, acetylcholinesterase (AChE) and α-glycosidase (α-gly) inhibition have emerged as a promising and important approach for pharmacological intervention in many diseases such as glaucoma, epilepsy, obesity, cancer, and Alzheimer's. In this manner, the preparation and enzyme inhibition activities of peripherally 1,2,3-triazole group substituted metallophthalocyanine derivatives with strong absorption in the visible region were presented. These novel metallophthalocyanine derivatives (2-6) effectively inhibited AChE, with Ki values in the range of 40.11 ± 5.61 to 78.27 ± 15.42 µM. For α-glycosidase, the most effective Ki values of compounds 1 and 2 were with Ki values of 16.11 ± 3.13 and 18.31 ± 2.42 µM, respectively. Also, theoretical calculations were investigated to compare the chemical and biological activities of the ligand (1) and its metal complexes (2–6). Biological activities of 1 and its complexes against acetylcholinesterase for ID 4M0E (AChE) and α-glycosidase for ID 1R47 (α-gly) are calculated. Theoretical calculations were compatible with the experimental results and these 1,2,3-triazole substituted phthalocyanine metal complexes were found to be efficient inhibitors for anticholinesterase and antidiabetic enzymes. Communicated by Ramaswamy H. Sarma
Keywords: Indoles; Enzyme Inhibition; Glycoside Hydrolases; Dft Studies; Isoindoles; Structure-Activity Relationship; DFT studies; Coordination Complexes; Hypoglycemic Agents; molecular docking; Molecular Biology; enzyme inhibition; Phthalocyanin etriazole enzyme inhibition molecular docking DFT studies; Phthalocyanine; molecular docking; Triazoles; Molecular Docking; Molecular Docking Simulation; triazole; Acetylcholinesterase; Triazole; Cholinesterase Inhibitors; 3. Good health